MATHEMATICAL MODEL OF' GAULTHERASE INACTIVATION KINETICS FOR THE GAULTHERIN PRODUCTION FROM WINTERGREEN (Gaulteria fragantissima) - Yulianto, Mohamad Endy Y; Hartati, Indah; yuniastuti, Ari (Universitas Diponegoro, 2007)
Abstract Wintergreen (Gaultheria fragantissima) is the source of the essential oil of wintergreen which is comprised predominantly of methyl salicylic. During this time wintergreen is not yet economically developed because of the lack of the cultivation technology. One of effort that is needed to be studied beside the cultivation tecnology and the wintergren oil quality development is the product diversification. wintergreen comprised by far the highest concentration of both free salicylic and total salicylic acid which is expected of a plant known for the formation of the wintergreen oil, an essential oil consisting primarily of methyl salicylic. The concentration of total salicylate found in wintergreen is over 20 fold greater than the total salicylic concentration (salicylic and any derivates combined) found in Filipendula, and 100 fold greater than that found in Lemon Thyme. The active form of salicylic acid in wintergreen is Gaultherin. Gaultherin has many properties related to human health. Gaultherin consists of methyl salicylic conjugated to the disaccharide, primeverose. When plant tissues are disrupted the endogenous gaultherin is rapidly lost, presumably by enzymatic hydrolysis with the release of methyl salicylic. The problem is until this time there is not yet available an effective method for the gaultherin extraction. The difficulties faced on the gaultherin production are the fact that along the gaultherin extraction. and along with the disruption of the wintergreen tissue, the gaultherin is hydrolyzed into its individual components which are methyl salicylic and disaccharide. The alternative process for the gaultherin production from wintergreen is the gaultherin production process by enzyme inactivation and extraction process in an inactivation extractor using a n organic solvent (alcoholic solvent extraction). This paper is intended to study the enzyme inactivation rate which is play an important role in the dimension determination of the process equipments. Enzyme inactivation can be describes as first orde reaction. The enzyme inactivation constant kp is the temperature, pressure, and water concentration function. The dependency, model of the temperature based on Arhenius type while the pressure dependency is based on Eyring equation. Keywords : gaultherin, inactivation. kinetics